A pilot study of intralesional ranibizumab on pterygium vascularity, size and recurrence rate - Chi, Ho Hao (2015)
Introduction: Pterygium is a common eye disorder in Malaysia due to the country’s location near to the equator. Recent study has found that vascular endothelial growth factor (VEGF) is present in great amount in pterygium epithelium especially in its head compared to normal conjunctiva suggesting that VEGF is involved in the angiogenesis and proliferative fibrovascular growth of pterygium. Thus, anti-VEGF has been proposed as an off-label adjunct to pterygium surgery. Objective: To evaluate the vascularity and size of primary pterygium after intralesional ranibizumab injection and the recurrence rate following sutureless pterygium surgery. Methodology: Patients presenting for primary pterygium excision who fulfilled our inclusion and exclusion criteria were identified. They were then randomised into treatment and control groups. Treatment group was injected with intralesional ranibizumab (0.3 mg/0.03 mL) 1 week prior to surgery. Anterior segment photographs were taken before and 1 week after the injection. Changes in pterygium vascularity (percentage of pterygium area covered by vessels) and size (percentage of cornea area covered by pterygium) were measured using image analysis software, Image J. 1 week after ranibizumab injection, both treatment and control groups underwent pterygium excision and conjunctiva autograft adhesion with fibrin glue. Patients were followed-up for 1 year to monitor for recurrence and complication. Results: 36 patients (18 each group) completed the study. Mean change in pterygium vascularity was 1.48 (4.65)% while pterygium size was 0.28 (2.71) %. Both reductions were not statistically significant (p = 0.195 and 0.672 respectively). Recurrence rate in treatment group was 22.2% (n = 4) while controlled group was 16.7% (n = 3). Recurrence rate between groups was not statistically significant (p > 0.950). Conclusion: Single intralesional injection of ranibizumab (0.3 mg/0.03 mL) did not reduce the pterygium vascularity and size significantly in 1 week time. Pre-operative intralesional ranibizumab did not reduce pterygium recurrence rate.